The Research guide A primer for residents, other health care trainees, and practitioners - Harvey, Bart J.; Lang, Eddy S.; Frank, Jason R.
A step-by-step guide for novice researchers and their supervisors. Written and reviewed by Canadian experts, this practical and accessible guide enables new and experienced researchers to effectively design a study, conduct the research and interpret the findings. Use as a stand-alone or modular curriculum.